Special regulation of agricultural business in the framework of sustainable agri-food system in Europe - Canfora, Irene (Przegląd Prawa Rolnego, 2022)
The article deals with the evolution of the Italian legislation on agricultural business and its legislative framework shaped in accordance with the development of the Common Agricultural Policy. The observed trends in legislation, both at the national and European level, confirm the special role of agricultural law, aimed at the maintenance of farmers activities based on the use of land as well as of the (European) agricultural production, destined for the food supply chain.